ASPEK KEUANGAN DALAM PERENCANAAN DAN PENGEMBANGAN BISNIS - Aziza Aziza; Afdho Ikhsan; M. Junaidi; Herman Herman; Rukayyah Rukayyah; Abshor Marantika (Jurnal Ekonomi Bisnis Kompetif, 2025)
This study aims to analyze the role of financial planning and management in supporting the sustainability of Micro, Small, and Medium Enterprises (MSMEs), as well as examining the obstacles faced and the role of digital technology as an innovative solution in financial management. This study uses a descriptive approach by analyzing the practices of financial planning, cash flow management, financial record keeping, and the use of digital technology by MSMEs. The results show that structured financial planning plays a crucial role in maintaining financial stability and business sustainability. However, MSMEs still face various obstacles, such as low financial literacy, mixing personal and business finances, limited access to formal financing, and weak cash flow management. The use of digital technology has proven to have significant potential in improving the efficiency, accuracy, and transparency of financial management, although its effectiveness is highly dependent on the readiness and understanding of business actors. This study concludes that strengthening financial planning supported by increased financial literacy, ongoing mentoring, and optimal use of digital technology is the main key to realizing the sustainability and competitiveness of MSMEs.